Electrophorectic pattern of the heat resistant proteins of corn seeds - José, Solange Carvalho Barrios Roveri; Pinho, Édila Vilela de Resende Von; Pinho, Renzo Garcia Von; Silveira, César Martoreli da (Pesquisa Agropecuaria Brasileira, 2005)
Several mechanisms are involved in the acquisition and maintenance of desiccation tolerance by the seeds. One of these mechanisms is related to the induction of heat resitant proteins. The objective of this work was to evaluate changes in the electophorectic patterns of the heat resistant proteins of corn seeds submitted to high drying temperature associating their expression with drying tolerance. Seeds of breeding lines, simple hybrids and respective reciprocals hybrids were utilized. The seeds were harvested with approximately 35% of water content and dried at 45°C. Seeds of lines dried under shadow were used as control and the physiological quality was evaluated by germination test. The heat resistant proteins were extracted from embryonic axis of seeds in Tris-HCl 0.05 M buffer. It was not possible to determine a specific band of heat resistant proteins which can be of use as a molecular marker of tolerance to high drying temperature. There was stability in the patterns of the bands of proteins of seeds submitted to artificial drying compared to the ones after shadow drying even for the lines of high variation in the germination values. The electrophorectic patterns of the heat resistant proteins were similar for both the hybrid seeds and respective reciprocals.